2017
DOI: 10.1007/978-94-024-1079-2_21
|View full text |Cite
|
Sign up to set email alerts
|

Taurine Directly Binds to Oligomeric Amyloid-β and Recovers Cognitive Deficits in Alzheimer Model Mice

Abstract: Alzheimer's disease (AD) is the most common cause of dementia leading to severe cognitive decline. During the progression of AD, amyloid-β (Aβ) monomers aggregate into neurotoxic soluble oligomeric Aβ that causes cognitive impairments. Our previous study indicates that oral supplementation of taurine at 1000 mg/kg/day significantly ameliorates hippocampal-dependent cognitive deficits in APP/PS1 transgenic AD mouse model. However, Aβ plaques and oligomeric Aβ levels are not affected after administration of taur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 15 publications
2
39
0
Order By: Relevance
“…Kim et al 40 reported that taurine significantly ameliorated hippocampus-related cognitive deficits in an AD mouse model. In another recent study, taurine was reported to bind directly to AβO and consequently ameliorated the behavioral deficiencies of AD, such as the loss of learning and memory 18 . Roberto et al 26 reported that taurine strongly protected neurons against the neurotoxicity of Aβ in vitro.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Kim et al 40 reported that taurine significantly ameliorated hippocampus-related cognitive deficits in an AD mouse model. In another recent study, taurine was reported to bind directly to AβO and consequently ameliorated the behavioral deficiencies of AD, such as the loss of learning and memory 18 . Roberto et al 26 reported that taurine strongly protected neurons against the neurotoxicity of Aβ in vitro.…”
Section: Discussionmentioning
confidence: 96%
“…Soluble AβO appears to be a more toxic and disease-relevant element in AD pathogenesis than plaques 47 49 . Jang et al 18 reported that taurine did not affect Aβ plaque levels in the APP/PS1 model but interacted directly with AβO, which led to enhanced memory function. Lesné et al 50 reported that Aβ plaques did not induce memory impairment in the absence of AβO in Tg2576 mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Representing a significant hallmark of NDs, this serves dual purpose, in the early-stage diagnosis of disease as well as in developing therapeutics for them. In the case of AD, taurine supplementation exerts its therapeutic effect by reducing Aβ aggregation [202]. Kim et al demonstrated that oral administration of taurine to a APP/PS1 transgenic mouse model relieves its cognitive defects via decreasing the Aβ levels [203].…”
Section: As Stabilizer In Regulating Protein Folding/unfoldingmentioning
confidence: 99%
“…Taurine is one of the most common free amino acids in the brain. Brain taurine levels are significantly decreased in AD, thereby preventing taurine's binding to oligomeric Aβ and its cognition-enhancing effects [169]. Taurine also attenuates Aβ42-induced mitochondrial dysfunction via SIRT1 induction [170] as well as modulating the gut microbiome and its influence on the immune system [171].…”
Section: Taurinementioning
confidence: 99%